How critical is the choice of distance-based measures in studying tumble turn performance? - Koster, P.; David, S.; Beek, P. J. (ISBS Proceedings Archive (Michigan), 2022)
The turn is a crucial part of swim races and therefore requires systematic investigation. Yet, many different measures of turn performance are used in the literature. This study aimed to examine the level of agreement and the sensitivity of six fixed-distance based performance measures of the tumble turn. Tumble turn data of 10 Dutch elite level swimmers were analysed using those measures. The overall level of agreement was high between all measures (R ranging from 0.91 to 0.99). However, if the swimmers were ranked according to each of those measures, not all performance measures resulted in the same ranking. In particular, the rankings for measures with an exist distance of 10 m deviated from those for measures with an exit distance of 5 or 15 m. This finding suggests that the performance measures of interest are sensitive to different phases of the turn.